Smoking Prevalence among Teenagers with Asthma in Lattakia Schools - ديب, غزل; الحكيم, أمل; حشمة, علا (Latakia University Journal -Medical Sciences Series, 2020)
Asthma is a widespread and chronic disease that affects adolescence and lifestyle effectiveness other than the enormous economic cost of treating cases and their complications in the short and long term.